Service Quality Analysis to Increase Customer Satisfaction at Minimart Located at Private University - Agapiou Sergios (Journal of Current Research In Multidisciplinary, 2023)
This research aims to analyze service quality to increase customer satisfaction at minimarkets. In this research, the sample of respondents used was 30 students. The sampling method used in this research was a purposive sample. The data used in this research uses primary and secondary data. Data was obtained through the results of distributing questionnaires. The data analysis technique uses quantitative methods, assisted by the importance performance analysis (IPA) method. based on the research results, the data are: Quadrant 1 which shows high importance low performance, things that need to be paid attention to because according to consumers it is important, quadrant 2 which shows high importance high performance where the performance and interests of consumers have been met well so it needs to be maintained, quadrant 3 which shows low importance low performance where the company's performance is not good but according to consumers is not important so it needs to be paid attention to but is not a priority, and finally quadrant 4 which shows low importance high importance things which according to consumers are not important but in terms of performance the company has done well. The results of the analysis that has been carried out show that there are several indicators that fall into quadrant 1, namely Q1 and Q2. Next, Q3, Q4, and Q7 enter Quadrant 2. Quadrant 3 only has one indicator, namely Q5, and the last quadrant contains four indicators, namely Q6, Q8, Q9, and Q10.